Tingkat Belanja Online Flash Sale Di Kalangan Guru MTs N 11 Pesisir Selatan - Efendi, Faisal; Mardianton, Mardianton; Sumarni, Ira; Nurlaila, Nurlaila; Ilham, Elgi Muhammad (Risalah Iqtishadiyah, 2023)
Research to determine the level of online shopping among MTsN 11 Pesisir Selatan teachers. Online shopping has become a habit or necessity for teachers. Principal, he said that almost every day an online package delivery courier comes to the school. Therefore, the author wants to examine the level of online shopping among teachers. This research uses a quantitative descriptive method by explaining data in the form of numbers into information. The objects of this research are teachers from various levels. The data collection technique was by distributing questionnaires via Google form with a total of 65 respondents consisting of civil servants, honorary teachers, and P3K, administrative employees. Data collection was carried out from July to early August 2023. The analytical tool used in this research used Microsoft Excel by distributing questionnaires via Google form to 65 respondents. The results of this research are that teachers often shop online at Shopee and Tiktok Shop stores by buying Fashion category products such as clothes, bags, shoes and others. Apart from that, they also buy skincare and makeup.